Relationship between Personality Types Conceptualized by C. G. Jung and Latvian IT Specialist Preferences - Maris Dargis; Anita Finke; Ludmila Penicina (Complex Systems Informatics and Modeling Quarterly)
General people’s personality types, as well as idiosyncrasies and cognition and perception characteristics specific to each type, are a common research item, especially in such areas as pedagogics, human resource management, etc. Personality traits characteristic for individuals and teams of certain specific avocations (i.e., project teams), however, are a much less explored subject. In this area, the amount of conducted research is congruent with the geopolitical location and directly correlates with the possibility of finding practical applications for the findings of said research. This study presents the initial findings of such research, within the scope of which the idiosyncrasies common for IT specialists were explored using the Myers-Briggs Type Indicator (MBTI) model. These initial findings can be used as the foundation for further study on the subject, helping to create a general Latvian IT specialist’s personality profile, and, possibly, identifying the areas that need development, while taking into consideration the tendencies and requirements of the Latvian IT market, as well as those of  the labour market worldwide.